Pelatihan Circulo Massage dan Sport Massage dalam Upaya Peningkatan Pengetahuan dan Keterampilan Masyarakat Kecamatan Guguak Panjang Kota Bukittinggi - Liza Liza; Aulia Asman (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Bukittinggi as a tourism industry, no wonder many local and foreign tourists who visit this city.Tourists who have traveled long distances to this city want to enjoy their vacation and the beauty of Bukittinggi City by releasing fatigue, with a fitness massage service. The many questions and requests of tourists visiting Bukittinggi City in terms of fitness massage services make a promising business opportunity for the people of Bukittinggi City, especially for the people of Guguak Panjang District which is right in the heart of Bukittinggi City. The method of implementing the activity is in the form of training and direct discussions about Circulo Massage and Sport Massage in the Guguak Panjang District community and continued with online monitoring and evaluation of exercises in an effort to train community skills to answer requests from tourists visiting Bukittinggi City. The number of training participants was 26 people consisting of cadre representatives from 7 Kelurahan in Guguak Panjang District. This activity was carried out on August 19, 2021. The results of the training activities showed that it increased the knowledge and skills of the people of Guguak Panjang District in Circulo Massage and Sport Massage.